Inflatable Jumping castles: advocacy in action. (1st March 2011) - Water, M; Stokes, M
Abstract : The use of inflatable jumping castles has directly led to the death and injury of children. In 2007 a child was killed in Budapest, with five others seriously injured when the toy inflatable jumping castle was blown more than 27 m in the air. In response to the death of a young girl in South Australia in 2001, a new standard was introduced in Australia in 2005, governing the manufacture of commercial inflatable jumping castles. However, this did not regulate all jumping castles classified as toys, nor regulate who classified jumping castles as toys. This facilitated some manufacturers to evade the standard, and sell unsafe devices to consumers. Collective data suggests as many as 2200 children across Australia were injured in the period 1996–2006. These injuries led to strong concern that domestic toy jumping castles may be more dangerous and be associated with increased injury risk to children. To address this Kidsafe Victoria developed and conducted an intensive awareness campaign during the period of July to October 2007. This involved direct lobbying of all relevant regulatory agencies and national media promotion to raise community awareness. Substantial media attention triggered action from the various National and regional consumer regulatory bodies (ACCC, CAV and Standards Australia), who all commenced internal investigations and intervened with public warning notices and advised that a dedicated standard would be written. This presentation will discuss the issue and the methodology behind the campaign and future implications for advocacy in child safety.